EFFECTIVE WAYS TO DEVELOP PROFESSIONAL TEACHERS OF FORMAL, INFORMAL AND NON-FORMAL EDUCATION IN THE SOUTH BENGKULU REGION, AND WEST JAVA PROVINCE CRISIS OF THE 21ST CENTURY - Amalliah Kadir (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
At the beginning of March 2020, the world is now being hit by the Covid-19 virus which makes the learning process of education an instant crisis. When educators, educational institutions, and anyone who has concerns in the field of education must address the problem of plurality in this country that is learning democracy. The world of education is facing the current globalization that has seeped into every life of our society. Educational Institutions in these regions are required to be able to respond to the enactment of the kemndikbud ristek nadiem Makarim policy on independent learning and about central and regional financial considerations so that the development of regional culture, Local education, and the management of our educational institutions remain good and also for the role of the government, the national education system, policies towards the world of education, procurement of school textbooks, and other points are able to overcome education problems in this crisis. Those are the points of concern that prompted the author to write an article on how to effectively develop professional teachers in times of crisis in the 21st century.